Mastering Autodesk Inventor : T-Splines (Infinite Skills, 2014)
"In this Inventor - T-Splines training course, expert author Paul Munford teaches you how to create and work with T-Splines in Autodesk Inventor. This course is designed for users that already have a basic working knowledge of Inventor. You will start by learning about the subdivision modeling primer, including CVs, control polygons, and troubleshooting T-Splines. Paul will then teach you how to use the T-Spline tools, such as how to add and remove symmetry from T-Spline surfaces, insert, sharpen, and crease edges, and add bridges and tunnels. Finally, this video tutorial will then teach you how to apply your knowledge of T-Splines by working on three projects: a spoon, a mug, and a saw. Once you have completed this computer based training course, you will have an in-depth understanding of how to create and use T-Splines in Inventor, and be able to apply this knowledge to your own projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.